2020
DOI: 10.1111/jre.12731
|View full text |Cite
|
Sign up to set email alerts
|

Glyburide inhibits the bone resorption induced by traumatic occlusion in rats

Abstract: Objective To examine whether glyburide inhibits bone destruction caused by traumatic occlusion in a rat occlusal trauma model. Background Excessive mechanical stress, such as traumatic occlusion, induces expression of IL‐1β and may be involved in bone resorption. NLRP3 inflammasomes have been linked to IL‐1β expression, but it is currently unclear whether glyburide, the inhibiter of NLRP3 inflammasome, suppresses occlusal trauma in rats. Methods Male SD rats aged 7 weeks were used. In the trauma group, the occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Excessive mechanical stress, including orthodontic movement and occlusal trauma, causes hyaline degeneration and can activate NLRP3 inflammasomes, increasing IL-1β expression in the periodontal apparatus. Glyburide, an NLRP3 inflammasome inhibitor, inhibited bone resorption by traumatic occlusion in rats by decreasing IL-1β tissue levels (Arita et al 2020).…”
Section: Il-1mentioning
confidence: 99%
“…Excessive mechanical stress, including orthodontic movement and occlusal trauma, causes hyaline degeneration and can activate NLRP3 inflammasomes, increasing IL-1β expression in the periodontal apparatus. Glyburide, an NLRP3 inflammasome inhibitor, inhibited bone resorption by traumatic occlusion in rats by decreasing IL-1β tissue levels (Arita et al 2020).…”
Section: Il-1mentioning
confidence: 99%
“…The qRT‐PCR and IHC results confirmed a sustained traumatic occlusal force throughout the experiment. Compared to the previously reported occlusal trauma experimental model, 22–27 this occlusal trauma model avoids several interference factors, such as resin abrasion, bad bonding and fixation of orthodontic wire, as well as the temporomandibular joint disorder in the experimental animals. Furthermore, the occlusal trauma model induced by metal crown bonding mimicked the clinical occlusal trauma disease.…”
Section: Discussionmentioning
confidence: 98%
“…NOD‐like receptor pyrin domain containing protein 3, as the upstream effector of caspase‐1, is considered to be another key molecule in pyroptosis, since it plays a key role in classical pyroptosis as a sensor of inflammation 43 . Recent studies have shown that glyburide inhibits bone resorption induced by occlusal trauma 22 . Here, we proposed a novel hypothesis stating that the clinical occlusal trauma with periodontitis leads to alveolar bone resorption through the NLRP3/caspase‐1/IL‐1β pathway.…”
Section: Discussionmentioning
confidence: 99%
“…NLRP3 inflammasomes have been linked to IL1b expression. Arita et al 254 examined whether glyburide could suppress occlusal trauma in rats (age 7 weeks). In the trauma group, wire was attached to maxillary right first molar occlusal surfaces resulting in occlusal trauma with mandibular right first molars.…”
Section: Bone Biology and Medication-related Osteonecrosis Of The Jawmentioning
confidence: 99%